2015
DOI: 10.1002/elan.201500529
|View full text |Cite
|
Sign up to set email alerts
|

Could Voltammetry be an Effective Alternative Technique to Study Adsorption Kinetics of Electroactive Metal Ions?

Abstract: The suitability of LSV to study adsorption kinetics of metal ions was evaluated using Cu2+ adsorption on Amberlite® IR‐120 as a model system. LSV provided results in agreement with conventional batch method with remarkable decreasing on analysis time and reagents consumption, since no adsorbent/adsorbate separation is required. Adsorption curves can be obtained in situ using only one portion of adsorbate solution. LSV provides higher temporal resolution for adsorption curves, which is indispensable to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…31 Oliveira et al 32 have demonstrated that Amberlite ® IR120 combined with carbon nanotubes was a very efficient chemical modifier for a CPE used for the simultaneous determination of Pb 2+ and Cd 2+ in ethanol fuel, gasoline for aviation and spiked water samples. Moreover, the literature 33 has reported that Amberlite ® IR120 presents both high metal accumulation capacity and high kinetic of adsorption for Cu 2+ , Zn 2+ and Cd 2+ . Therefore, the Amberlite ® IR120 has a great potential as a chemical modifier able to promote the formation of NBi on the CPE surface after an electrochemical reduction step.…”
Section: Introductionmentioning
confidence: 99%
“…31 Oliveira et al 32 have demonstrated that Amberlite ® IR120 combined with carbon nanotubes was a very efficient chemical modifier for a CPE used for the simultaneous determination of Pb 2+ and Cd 2+ in ethanol fuel, gasoline for aviation and spiked water samples. Moreover, the literature 33 has reported that Amberlite ® IR120 presents both high metal accumulation capacity and high kinetic of adsorption for Cu 2+ , Zn 2+ and Cd 2+ . Therefore, the Amberlite ® IR120 has a great potential as a chemical modifier able to promote the formation of NBi on the CPE surface after an electrochemical reduction step.…”
Section: Introductionmentioning
confidence: 99%
“…Electroanalytical techniques have a great potential to become the technique of choice for the real-time tracking of active processes, such as drug release from nanoparticles, 1,2 the kinetics and thermodynamics of formation and the decay of nanoparticles, 3 cell apoptosis, 4 dopamine release from brain tissue, 5 and adsorption processes. 6,7 Since 1970s, with the development of more sensitive electronics, the applications of ISEs have expanded tremendously. The solid contact screen printed ion-selective electrodes (SC-SP-ISE) have emerged as an essential technique of the potentiometric electrochemical analysis with hundreds of publications.…”
Section: Introductionmentioning
confidence: 99%